Dividend Policy in Indonesian Infrastructure Firms: Evidence on the Moderating Role of Profitability - Delita Br Gultom; Noor Salim (ACCOUNT: Jurnal Akuntansi, Keuangan dan Perbankan, 2026)
This study was conducted to investigate the effects solvency, liquidity, company growth, and company size on dividend policy, with profitability functioning as a moderating variable among infrastructure sector firms that were registered on the Indonesia Stock Exchange during the 2021-2023 period. A quantitative approach was adopted in this study, and the data were gathered from the annual financial statements of the sampled companies as secondary sources. The research sample was determined to consist of 18 companies, yielding 53 final observations that were selected by means of purposive sampling. Multiple linear regression alongside Moderated Regression Analysis (MRA) were employed as analytical methods, assisted by SPSS 20 software. The findings revealed that liquidity and company size exerted a notably positive influence on dividend policy, whereas solvency and company growth were found to demonstrate no significant effect on dividend policy. Profitability was found to significantly moderate the adverse influence of liquidity on dividend policy, yet was not found to significantly moderate the impacts of solvency, company growth, and company size on dividend policy. Keywords: Dividend policy; solvency; liquidity; company size; profitability